Structural Analysis of a Tale from Kathmandu - Subedi, Narendra Raj (Interdisciplinary Journal of Management and Social Sciences, 2023)
Folk tales are part and parcel of human life because they have been told and retold in every human society from the time immemorium. Though its not clear when and how they have been an intrinsic part of human life. This is a treasure and specially the treasure of language which have been bestowed by our ancestors. Since the folk tales are part of the folk literature, they have drawn the attention of the folklorists. Folklorists have studied, analyzed, interpreted and researched on the different genres of folk literature and the folk tale is one of them. They are simple narrative. They are simple, short and having unique structure which enthrall listeners and also encourage the tellers to tell them again and again nevertheless even at our age of science and technology. Nepali society is multi-ethnic, multi-cultural and diverse in nature. They have their folktales to entertain and heal the psychological burden too. The present research tries to analyze the folktales of Kathmandu/Nepal from the structural approach. The present research claims that the structures of folktales are the main cause of bringing effects on both tellers and the listeners. This research will take help of the idea/theory developed by Vladimir Propp whose Morphology of Folktale will be the methodology to analyze the structure of the folktale.